A Transdiagnostic group therapy for sleep and anxiety among adults with substance use disorders: Protocol and pilot investigation - Milanak, Melissa E.; Witcraft, Sara M.; Park, Jie Young; Hassell, Katharine; McMahon, Tierney; Wilkerson, Allison K. (Frontiers in Psychiatry, 2023)
Introduction: Treatment of substance use disorders (SUDs) is challenging with high rates of treatment dropout and relapse, particularly among individuals with comorbid psychiatric conditions. Anxiety and insomnia are prevalent among those with SUD and exacerbate poor treatment outcomes. Interventions that concurrently target anxiety and insomnia during the early stages of SUD treatment are lacking. To this end, we investigated the feasibility and preliminary effectiveness in a single arm pilot trial of an empirically informed group transdiagnostic intervention, Transdiagnostic SUD Therapy, to concurrently reduce anxiety and improve sleep among adults receiving treatment for SUD. Specifically, we hypothesized that participants would evidence declines in anxiety and insomnia and improvements in sleep health, a holistic, multidimensional pattern of sleep-wakefulness that promotes wellbeing. A secondary aim was to describe the protocol for Transdiagnostic SUD Therapy and how it may be implemented into a real-world addiction treatment setting. Method: Participants were 163 adults (Mage = 43.23; 95.1% White; 39.93% female) participating in an intensive outpatient program for SUD who attended at least three of four Transdiagnostic SUD Therapy sessions. Participants had diverse SUDs (58.3% alcohol use disorder, 19.0% opioid use disorder) and nearly a third of the sample met criteria for two SUDs and comorbid mental health diagnoses (28.9% anxiety disorder, 24.6% major depressive disorder). Results: As anticipated, anxiety and insomnia reduced significantly across the 4-week intervention period from clinical to subclinical severity, and sleep health significantly improved (ps < .001). These statistically significant improvements following Transdiagnostic SUD Therapy demonstrated medium to large effects (ds > 0.5). Conclusions: Transdiagnostic SUD Therapy is designed to be flexibly administered in ‘real-world’ clinical settings and, preliminarily, appears to be effective in improving emotional and behavioral factors that increase risk for return to substance use and poor SUD treatment outcomes. Additional work is needed to replicate these findings, determine the feasibility of widespread uptake of Transdiagnostic SUD Therapy, and examine whether the treatment effects translate to improvement in substance use outcomes.